Manajemen Bisnis Syariah dalam Kehidupan Sehari-hari - Arum, Tantri; Rialdy, Novien (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to examine the application of sharia business management in everyday life. The main focus of the study is how sharia principles are applied in various aspects of business, including transactions, business management, and the relationship between business owners and employees. With a qualitative approach, this study analyzes relevant literature to explore the benefits and challenges in implementing sharia business management. The results of the study indicate that the application of sharia principles, such as honesty, fairness, and transparency, can improve the relationship between business owners and consumers, as well as create a fairer and more sustainable economic system.